Effect of melting pressure and superheating on chemical composition and contamination of yttria coated ceramic crucible induction melted titanium alloys - Gomes, Fernando (2011)
When melting reactive alloys, chemical composition and alloy homogeneity strongly depend on processing conditions, especially if melting is performed in ceramic crucibles. In this case, the nature of crucible materials, the melting stock composition and the melting parameters (atmosphere, pressure, superheating time and temperature) are critical processing variables. In this work, a Ti–48Al alloy was induction melted in a ZrO2 SiO2-based crucible with Y2O3 inner layer using different superheating temperatures (1600 and 1650 C) and times (0, 60 and 90 s) and poured into a graphitemould. The influence of different temperature/time combinations in the alloy composition, Al loss by evaporation and metal/crucible interaction was studied for different melting pressures. Al loss was found to increase significantly for melting pressures below 10-2 mbar and increases with increasing superheating time and temperature. The experimental results concerning to Al loss are in agreement with theoretical (and experimentally validated) models available for induction skullmelting of TiAl.Metal/crucible interaction directly increased with melting pressure, superheating time and temperature, leading to alloy contamination withYand O. For the experimental set-up used in this work, optimal temperature/ superheating time/pressure combinations that lead to acceptable alloy composition have been identified.